Nano-Selenium and Nano-Curcumin Supplementation Effect on Liver Function in Broiler Chickens - , H. S.Shwetha; M. Narayana Swamy; B. Srinivas Reddy, M. K.Vinuthan; A, SAHADEV; E, Preediya BABU; D, RAJENDRAN (Indian Journal of Animal Nutrition, 2023)
The present study was designed to compare impact of dietary supplementation of different sources of Se on growth performance, Se concentration of breast meat, and immune response of broiler chickens The present study was designed to compare the impact of dietary supplementation of different sources of Se on growth performance, Se concentration of breast meat, and immune response of broiler chickens. A total of 360-day-old broiler chicks were randomly divided into four groups with each group comprising 90 chicks. Group I chicks stood as control with a standard broiler diet. Groups II, III, and IV were supplemented with nano-Se (0.3 mg/kg diet), nano-curcumin (200 mg/kg diet), and a combination of both nano-Se (0.15 mg/kg diet) and nano-curcumin (100 mg/kg diet) along with basal diet, respectively. Blood samples were collected on 21st, 28th, 35th, and 42nd days and processed for serum samples. Liver enzymes, glucose, and total protein profile were estimated by using the spectrophotometric method. Serum alanine transaminase (ALT) activities were significantly lower in supplemented groups compared to control groups. Significantly lower serum aspartate aminotransferase (AST) activities were observed in Group III and Group IV when compared to Group I. Non-significant (p < 0.05) differences were observed in the activity of serum gamma-glutamyl transferase (GGT), lactate dehydrogenase (LDH), glucose, total protein and albumin between the nanoparticles supplemented groups and control group at different days of observation. Thus, the inclusion of Nano-Se and nano-curcumin has a better effect on liver function in broiler chickens. The evidence in this study can help to design research trials in the poultry industry.